Primitive myxoid mesenchymal tumor of infancy, an enigmatic entity: A case report - Malini Goswami (Indian Journal of Pathology and Microbiology)
Primitive myxoid mesenchymal tumor of infancy (PMMTI) is a rare soft tissue neoplasm of intermediate malignant potential occurring predominantly in infants and younger children. It can show aggressive local infiltration of surrounding structures and frequent relapses but rare metastasis. Morphologically, it is characterized by a proliferation of immature mesenchymal cells in a myxoid background with mild cytologic atypia and branching vessels. The tumor cells demonstrate immunoreactivity with vimentin and BCOR, however, are negative for more specific lineage markers. Its molecular hallmark is BCOR-internal tandem duplication. Previously classified as infantile fibrosarcoma/undifferentiated sarcoma, the association with BCOR-ITD has led to its reclassification as part of a distinct entity—”Sarcoma with BCOR Genetic Alterations”—in the 2020 WHO Classification of Soft Tissue Tumours. Here is a report of a case of a 2-year-old boy with a recurrent scalp mass identified as a primitive myxoid mesenchymal tumor of infancy.